Analysis of Running Techniques and Physical Factors on the Sprinter Ability of Grade V Elementary School - Sipriadi, Helpi; Imansyah, Farizal; Rizhardi, Rury (PPSDP International Journal of Education, 2024)
This study investigates the relationship between running techniques, physical factors, and the sprinting abilities of fifth-grade elementary school students. Through direct observation and measurement of students’ running techniques, as well as assessments of their physical attributes such as speed, leg muscle strength, and flexibility. This research aims to identify key factors that contribute to sprinting performance. Statistical analysis reveals a significant positive correlation between proper running techniques characterized by a forward-leaning posture, synchronized arm-leg movements, and correct foot landing and enhanced sprinting ability. Furthermore, the analysis highlights the importance of physical factors, with findings showing that students possessing greater leg muscle strength and flexibility exhibit superior sprinting capabilities. The correlation analysis underscores the strong influence of both running techniques and physical attributes on sprinting performance, indicating that improvements in these areas can lead to enhanced athletic outcomes. These findings have practical implications for the development of targeted training programs in elementary schools, emphasizing the enhancement of running techniques and physical conditioning. By focusing on structured training that incorporates muscle strengthening, flexibility improvement, and technique refinement, educators can help students maximize their athletic potential and encourage lifelong healthy habits. This research contributes to a deeper understanding of the factors influencing sprinting abilities and offers a foundation for optimizing physical education practices for young athletes.